Downregulation of HNRNPK in human cancer cells inhibits lung metastasis - Li, Mengyuan (Animal Model Exp Med, 2019)
BACKGROUND: Lung cancer frequently occurs in the clinic, leading to poor prognosis and high mortality. Markers for early diagnosis of lung cancer are scarce, and further potential therapeutic targets are also urgently needed. METHOD: We established a new mouse model in which the specific gene HNRNPK (heterogeneous nuclear ribonucleoprotein K) was downregulated after administration of doxycycline. The lung metastatic nodules were investigated using bioluminescence imaging, micro‐CT, and autopsy quantification. RESULTS: Compared with the short hairpin negative control group, less lung metastatic nodules were formed in the short hairpin RNA group. CONCLUSION: Downregulation of HNRNPK in cancer cells can inhibit lung metastasis.